Emission factors of organic carbon and elemental carbon for residential coal and biomass fuels in China- A new database for 39 fuel-stove combinations. (October 2018) - Sun, Jianzhong; Zhi, Guorui; Jin, Wenjing; Chen, Yingjun; Shen, Guofeng; Tian, Chongguo; Zhang, Yuzhe; Zong, Zheng; Cheng, Miaomiao; Zhang, Xinmin; Zhang, Yang; Liu, Chunyu; et al.
Abstract: In recent years many households in northern China's rural areas tend to furnish their houses with water-circulating piping system for heating, which entails mini-boiler stoves to heat water via raw coal chunk or biomass pellets. In this study, consistent efforts were made to obtain first-hand emission factors of organic carbon (EFOC ) and elemental carbon (EFEC ) for residential solid fuel combustion. A total of 39 fuel/stove combinations, covering seven coals (with different geological maturities), eleven biomass fuels, and five different stoves, were tested. The mean EFOC and EFEC were (4.29 ± 2.33) and (4.43 ± 2.18) g/kg for residential coal combustion, (2.16 ± 4.47) and (0.42 ± 1.01) g/kg for indoor biomass burning. The EFs for tested coal combustion display a "bell shape" with the maximum EF value occurring at bitumite of middle maturity. Coal briquetting in this study led to a significant decrease in EFEC but a notable increase in EFOC, which contradicted with the result from some of previous studies that coal briquetting always leads to relatively low emissions of both OC and EC. The inside reason deserves further clarification. Averaging over the two mini-boiler stoves shows that the introduction of mini-boiler stoves can reduce 5% and 10% of OC from anthracite and bitumite, respectively, and 47% and 53% of EC from anthracite and bitumite, respectively, suggesting that transfer from pure heating stoves to mini-boiler stoves seems unlikely to increase carbonaceous particle emissions, particularly EC. The more significant decline in EFEC than in EFOC indicates that the access to mini-boiler stove for winter heating is very likely to be both a clean air measure and a warming mitigation approach. Updated emission inventories in China for the year of 2014 showed that the OC and EC emissions were 338 Gg and 529 Gg, respectively, from residential coal combustion, and 557 Gg and 79 Gg, respectively, from household biomass burning. Highlights: Significant changes in the combustion pattern of household solid fuels in China. A new database of EFOC and EFEC for household coals and biomass fuels acquired. Middle volatile bituminous coals having highest EFOC and EFEC reconfirmed. A decrease in EFEC but an increase in EFOC due to briquetting. Lower particulate carbon emissions for biomass pressed pellets than for raw biomass.